Policing, recognition, and belonging - Loader, I (2006)
In this article, the author reflects on the question of how policing institutions can help to foster and sustain the values and practices of democracy. The author's overarching concern is to outline and defend a conception of democratic policing that highlights the role of policing agencies in recognizing the legitimate claims of all individuals and groups affected by police actions and affirming their sense of belonging to a political community. From this perspective, the author offers a critique of certain prominent forms of what he calls "ambient policing" and aims to cast some new light on the issue of how policing contributes to - or undermines - citizen security in democratic societies.